The impact of self assessment on the second language writing of undergraduates - Sivaji, K. (University of Jaffna, 2012)
This study presents the findings of a classroom research carried out to investigate the effect of Self Assessment on the Second Language Writing of Undergraduates. Second language (L2) writing depends on the variety of background experience, needs, interests and purposes for writing and these aspects play a vital role in second language writing situations than in first language. Thus second language writers in the research context, the University of Jaffna, face challenges in developing writing skills. The ability to produce accurate writing needs to be developed among these undergraduates. As many of the writings are difficult to understand due to grammatical inaccuracies and incorrect organization, this study was designed to investigate a suitable technique to improve these students’ L2 writing. Hence this study attempted to find out the effect Self Assessment had on students’ writing. In this study, self assessment is defined as a type of autonomous feedback the learner achieves on learning progress. Twenty four third year undergraduates in the Faculty of Arts, University of Jaffna who were specializing in social sciences were selected among a total population of ninety seven students. The group was treated with free writing activities, self assessment sessions and remedial steps. Students` attitude on self assessment was also investigated through a questionnaire. The results revealed that Self Assessment had a positive impact on students` writings and students revealed a positive attitude to Self assessment. Irrespective of gender, both male and female students were able to improve their writing ability. The study has important implications for ESL teachers who teach writing at the University of Jaffna in particular and at other universities across the island.
Keywords: Autonomous feedback; Grammatical inaccuracies; Organisation of writing; Second language (L2) writing; Self assessment